2019
DOI: 10.1155/2019/6416187
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response of Piglets Receiving Mixture of Formic and Propionic Acid Alone or with Either Capric Acid or Bacillus Licheniformis after Escherichia coli Challenge

Abstract: This study aims to evaluate whether diets containing mixture of formic and propionic acid alone or supplemented with either capric acid or Bacillus Licheniformis can alleviate immune inflammatory response of piglets challenged with enterotoxigenic Escherichia coli (ETEC). A total of 30 weaning pigs were assigned to 5 diets, without additive (CON), with antibiotics (ATB), with 1% organic acid (OA; 64% formic and 25% propionic acid), with OA plus 0.2% capric acid (OA + CRA), and with OA plus 0.02% probiotic (Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The dose of inoculum used in this trial was based on a previous trial by our group [28], however, it was low if compared to other trials [35][36][37]. Nevertheless, the challenge seemed to be effective at increasing the diarrhea among the piglets as higher values were observed for the first period evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of inoculum used in this trial was based on a previous trial by our group [28], however, it was low if compared to other trials [35][36][37]. Nevertheless, the challenge seemed to be effective at increasing the diarrhea among the piglets as higher values were observed for the first period evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli K88 (CVCC225) was purchased from the Chinese Veterinary Medicine Collection Center, and it was confirmed to have heat labile enterotoxin (LT), heat stable enterotoxin (ST), and F4 fimbriae in our laboratory ( Ren et al, 2019 ). On day 12, piglets from the ETEC, ATB, and AN group orally challenged with 10 mL nutrient broth (NB) containing 5 × 10 9 CFU/mL ETEC K88 via a syringe, CON group orally injected with 10 mL of sterilized NB.…”
Section: Methodsmentioning
confidence: 99%
“…A few studies in piglets experimentally challenged with E. coli F4 demonstrated that mixtures of short chain fatty acids (SCFA) can decrease diarrhea severity, improve growth performance, and reduce fecal E. coli counts [130,164]. Moreover, it was also demonstrated that a complex of SCFA with capric acid (a medium chain fatty acid) can significantly alleviate the inflammatory response in piglets challenged with E. coli F4 [165], remarkably reducing TNF-α and IFN-γ plasma levels. These findings ascribe OA as powerful alternatives to manage PWD, even if further studies are required to fully understand the effectiveness of OA to completely replace pharmacological doses of Zn.…”
Section: Organic Acidsmentioning
confidence: 99%